1997
DOI: 10.1097/00005176-199703000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Platelet-Activating Factor Receptor Antagonist WEB 2170 Prevents Neonatal Necrotizing Enterocolitis in Rats

Abstract: The data support the role of PAF in the final common pathway of neonatal NEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Altered PAF metabolism has been associated with NEC in human studies and animal experiments (3,4). For example, using the same NEC animal model we used in the present study, pups treated with the PAFR antagonist WEB 2170 and PAF-degrading enzyme PAF-AH had a lower incidence of NEC.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Altered PAF metabolism has been associated with NEC in human studies and animal experiments (3,4). For example, using the same NEC animal model we used in the present study, pups treated with the PAFR antagonist WEB 2170 and PAF-degrading enzyme PAF-AH had a lower incidence of NEC.…”
Section: Discussionmentioning
confidence: 60%
“…One of the key inflammatory mediators associated with NEC is PAF. Studies have shown that PAFR blockade or enhanced intestinal PAF degradation via PAF acetylhydrolase (PAF-AH) supplementation reduces the incidence of NEC in a neonatal rat model, and this experimental model resembles the clinical and pathologic features quite similar to human neonatal NEC (3,4).…”
mentioning
confidence: 99%
“…These include anti-TNF-α [82] , PAF receptor antag onists [203] , heparin-binding EGF-like g rowth factor [204] , anti-inflammator y cytokines (IL-10) [205] , pentoxifylline [206] , intestinal trefoil factor 3 [207] , and glucagon-like peptide 2. Recent research has identified that complex glycosphingolipids in the form of gangliosides act as bioactive factors down-regulating many acute proinflammatory signals in the intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…Additional experiments have evaluated the importance of PAF in neonatal rats using the typical risk factors of NEC, including asphyxia and formula feeding [16]. In this model, we have shown that PAF receptor blockade reduces the incidence of NEC, and that the PAF-degrading enzyme PAF-AH given with enteral feeding interferes with the initiation of NEC [17,18]. Breast milk, which is thought to reduce the risk for NEC, contains significant quantities of this enzyme.…”
Section: The Role Of Platelet Activating Factor Homeostasismentioning
confidence: 99%